MARAKNYA PELANGGARAN KESANTUNAN BERBAHASA SARKASME DALAM KOLOM KOMENTAR TIKTOK AKUN @DENISE.CHARIESTA - Mellyonisa Athariq Samsulhadi; Atiqa Sabardila (TOTOBUANG, 2022)
This article aims to describe the sarcasm figure of speech used in commenting on Tiktok accounts and then analyze it into the form of language politeness violations and what factors support language politeness violations. This study uses a data analysis method by collecting data and then presenting a description of the situation under study in the form of a narrative. The researcher records the data in the form of speech in the form of uploading comments and then analyzes it so that conclusions can be drawn. The result of this research is the common use of sarcasm figure of speech used in commenting, where the speaker mostly ignores the feelings of the interlocutor. The use of sarcasm that is widely used in comments is the cause of the violation of language politeness. Several factors that cause language politeness violations, namely, showing the existence of netizens, expressing expressions, non-face to face communication, behavior in use, and social media. The results of this study conclude that many comments on Denise Chariesta's tiktok account violate the principles of politeness in language conveyed by Leech.